Transition from vocational education and training to higher education in Germany and Switzerland - a perspective of social inclusion and exclusion - Siecke, Bettina [Verfasser] (My University, 2011)
This contribution compares the transition from a completed apprenticeship to higher education in Germany and Switzerland. The main focus is laid on the impact of social inclusion and exclusion in this transition process. (BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.1 Deutschland; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Ausgrenzung; Internationaler Vergleich; Bundesrepublik Deutschland; Schweiz